2020
DOI: 10.1177/1745691620927674
|View full text |Cite
|
Sign up to set email alerts
|

Tilting at Windmills: Why Attacks on Repression Are Misguided

Abstract: In the November 2019 issue of Perspectives, Otgaar et al. argued that the “memory wars” persist and that “the controversial issue of repressed memories is alive and well and may even be on the rise” (p. 1072). Their thesis overlooked the well-established consensus that recovered memories of trauma may be genuine, false, or a mixture of the two and instead focused on a disputed mechanism: unconscious repression. A formal cocitation analysis identified the major publications mentioning repressed memories, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 105 publications
(124 reference statements)
1
10
0
Order By: Relevance
“…(p. 4) These authors endorse the idea of unconscious repression (e.g., "eruption into consciousness of memories that had been entirely repressed"). Likewise, although we agree with Brewin (2021) that "clinical evidence" (p. 443) shows that there are many types of memories elicited without suggestion, "clinical evidence" is no guarantee that recovered memories are true.…”
Section: What Do Scholars Mean By Repressed Memory?supporting
confidence: 54%
See 2 more Smart Citations
“…(p. 4) These authors endorse the idea of unconscious repression (e.g., "eruption into consciousness of memories that had been entirely repressed"). Likewise, although we agree with Brewin (2021) that "clinical evidence" (p. 443) shows that there are many types of memories elicited without suggestion, "clinical evidence" is no guarantee that recovered memories are true.…”
Section: What Do Scholars Mean By Repressed Memory?supporting
confidence: 54%
“…In a previous review, we ( Otgaar et al, 2019 ) concluded that the controversial issue of unconscious blockage of psychological trauma or repressed memory remains very much alive in clinical, legal, and academic contexts. In response to our claim, Brewin (2021) offered evidence that he argued is “incompatible” (p. 449) with our conclusions. For example, Brewin claimed that few if any scholars refer to unconscious repression.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Rather than continuing to assert that "the belief in the scientifically controversial phenomenon of repressed memory remains widespread among the general public" (p. 1999), we urge Otgaar et al to reflect on the fact that recovered memories are a reasonably common therapeutic phenomenon that does not invariably involve sexual abuse, and is largely unrelated to therapists' beliefs in repression or use of inappropriate therapeutic techniques (Andrews et al, 1999;Brewin, 2020;Brewin & Andrews, 1998;Dodier, Patihis, & Payoux, 2019). Given this, and the technical nature of the subject, it is not surprising that the attempt to reduce complex situations to simple questionnaire items with limited response options has not been productive and has not led to meaningful results.…”
mentioning
confidence: 99%
“…This was a category error, confusing the observed phenomenon (forgetting of trauma) with a possible mechanism (Brewin & Andrews, 1998; Lindsay & Briere, 1997). It was also a red herring (i.e., an idea that distracts people from the central point being considered), in that no publications by clinicians that endorsed unconscious repression as responsible for this forgetting were cited by Loftus at the time or have come to light subsequently (Brewin, 2020). Today there is no debate, either among professional bodies or independent commentators, over the fact that recovered memories of traumatic events may be true, false, or a mixture of the two (Belli, 2012; Lindsay & Read, 1995; McNally & Geraerts, 2009).…”
mentioning
confidence: 99%